1984
DOI: 10.1038/308247a0
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of nucleosomes and linker DNA in calf thymus chromatin determined by photochemical dichroism

Abstract: The dichroism for photochemical attachment of a psoralen derivative to Mg2+-stabilized chromatin fibres is used to deduce the orientation of nucleosomal disks and linker DNA in the 30-nm fibre. The new technique of photochemical electric dichroism should have general applicability to problems of nucleic acid organization in cellular subunits and viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…To avoid steric clashes the model also incorporates a nucleosome tilt of 17°in relation to the fiber axis. This value corresponds well to the range (13°to 38°) measured for chromatin isolated from a number of different species by using both electric (28,29) and photochemical dichroism (30,31). The proposed nucleosome packing arrangement can easily be extended to the 44-nm fiber because the concomitant increase in volume and mass per unit length would result in an essentially constant nucleosome density.…”
Section: Discussion Chromatin Fibers Form Two Discrete Structural Clasupporting
confidence: 83%
See 1 more Smart Citation
“…To avoid steric clashes the model also incorporates a nucleosome tilt of 17°in relation to the fiber axis. This value corresponds well to the range (13°to 38°) measured for chromatin isolated from a number of different species by using both electric (28,29) and photochemical dichroism (30,31). The proposed nucleosome packing arrangement can easily be extended to the 44-nm fiber because the concomitant increase in volume and mass per unit length would result in an essentially constant nucleosome density.…”
Section: Discussion Chromatin Fibers Form Two Discrete Structural Clasupporting
confidence: 83%
“…During the past three decades evidence from EM (14-23), x-ray and neutron scattering (24)(25)(26)(27), electric and photochemical dichroism (28)(29)(30)(31), sedimentation analysis (32)(33)(34)(35), nuclease digestion (6,9,36), and x-ray crystallography (4,5,37,38) has led to the proposal of a number of different models for the 30-nm fiber. These models fall into two main classes: the one-start helix or solenoid models, and the two-start helix models.…”
mentioning
confidence: 99%
“…These values are substantially greater than the average curvature of DNA wrapped around the histone octamer (54,55) and indicate that HMG-D bound DNA is not smoothly curved. In the context of linker DNA, such a state would be consistent with both the lack of UV-induced thymine dimer formation in the linker (56) and also, with evidence from electric dichroism studies, that the trajectory of linker DNA differs from that of DNA bound to the core histones (57). Of particular relevance are the observations of Hamiche et al (58), who showed that, in the presence of histone H1 derivatives containing a major proportion of the basic C-terminal domain, the linker DNA enters and leaves a single chromatosome as a straight rod approximately perpendicular to the superhelical axis.…”
Section: A Role For Hmg-d As a Linkersupporting
confidence: 64%
“…One parameter of isolated compact fibers that has been estimated from electric dichroism measurements is the tilt angle of the nucleosomal disk with respect to the fiber axis (24)(25)(26). In the modeled system, there is a simple linear relationship between ( and nucleosome tilt, values of 00 (and 3600) for , ( resulting in nucleosomes oriented perpendicular to the fiber axis, whereas for (3= 1800, the nucleosome disks are parallel to the axis (see Fig.…”
Section: Resultsmentioning
confidence: 99%